ANALISIS PEMAHAMAN PETANI TENTANG PENGOLAHAN HASIL PERTANIAN SEBAGAI UPAYA DIVERSIFIKASI EKONOMI DI DESA LUBUK SEBERUK OKI - Khusnia, Siti; Khaq, Ahmad Rizalul; Ma'ruf, Imam Ali (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstrack: This study addresses the strategic issue of low utilization of agricultural product processing among farmers in Lubuk Seberuk Village, Ogan Komering Ilir (OKI) Regency. The main objective of this study is to understand the extent to which farmers in the region possess the knowledge, attitudes, and readiness to develop value-added agricultural product-based businesses. The study employed a descriptive qualitative approach, exploring farmers' views, attitudes, and practices related to agricultural product processing. Data were obtained through direct observation and in-depth interviews. Data analysis followed the stages of Miles and Huberman, namely data reduction, data presentation, and systematic and reflective conclusion drawing. The results indicate that the majority of farmers have initial awareness of the potential of agricultural product processing but have not yet been fully able to apply it. The main inhibiting factors include limited access to processing technology, minimal technical training, limited capital, and the government's suboptimal role in supporting agricultural-based economic diversification programs. Nevertheless, some farmers have taken the initiative to independently process their crops into products such as chips, flour, and other packaged products that are marketed locally and online. This step has been proven to increase income and open up new business opportunities in rural areas. Keywords: Agricultural Product Processing, Farmer Understanding, Economic                  Diversification Abstrak: Penelitian ini mengangkat isu strategis terkait rendahnya pemanfaatan pengolahan hasil pertanian di kalangan petani di Desa Lubuk Seberuk Kabupaten Ogan Komering Ilir (OKI). Tujuan utama penelitian ini adalah untuk memahami sejauh mana petani di wilayah tersebut memiliki pengetahuan, sikap, dan kesiapan dalam mengembangkan usaha berbasis olahan hasil pertanian yang bernilai tambah. Penelitian menggunakan pendekatan kualitatif deskriptif, yaitu dengan mengeksplorasi pandangan, sikap, dan praktik petani terkait proses pengolahan hasil pertanian. Data diperoleh melalui observasi langsung, wawancara mendalam. Analisis data mengikuti tahapan Miles dan Huberman, yaitu reduksi data, penyajian data, dan penarikan kesimpulan secara sistematis dan reflektif. Hasil penelitian menunjukkan bahwa mayoritas petani telah memiliki kesadaran awal mengenai potensi pengolahan hasil pertanian, namun belum sepenuhnya mampu mengaplikasikannya. Faktor penghambat utama meliputi keterbatasan akses terhadap teknologi pengolahan, minimnya pelatihan teknis, keterbatasan modal, dan belum optimalnya peran pemerintah dalam mendukung program diversifikasi ekonomi berbasis pertanian. Meskipun demikian, beberapa petani telah mengambil inisiatif mandiri untuk mengolah hasil panen menjadi produk seperti keripik, tepung, dan olahan kemasan lain yang dipasarkan secara lokal maupun daring. Langkah ini terbukti menambah penghasilan dan membuka peluang usaha baru di pedesaan. Kata kunci: Pengolahan Hasil Pertanian, Pemahaman Petani, Diversifikasi Ekonomi.